New Advances on Fermentation Processes - María Martínez-Espinosa, Rosa (IntechOpen, 2020)
In recent years, there has been an increase in the concern of society and industries about how food and beverages are produced, the production of natural compounds as well as the concern of industries on fermentation-based processes. Thus, there are several approaches worldwide that are looking for low time and low cost fermentation-based processes integrating not only molecular biology procedures but also engineering. This book contains eleven chapters written by international experts in the field of fermentation. It covers all recent aspects on fermentation-based processes with potential applications in many fields such as bio combustible production, food and beverage processing, and biomedicine.